2005
DOI: 10.3844/ajidsp.2005.50.54
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Syringe Sharing Among Users of a Medically Supervised Safer Injecting Facility

Abstract: Vancouver, Canada recently opened a medically supervised safer injecting facility (SIF) in an effort to reduce HIV and overdose risk and public injection drug use. We sought to examine factors associated with syringe sharing among SIF users. SIF users were randomly recruited into a prospective cohort of SIF users known as the Scientific Evaluation of Supervised Injecting (SEOSI) cohort. We examined the prevalence and correlates of used syringe borrowing among baseline HIV-negative participants and used syringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…In communities centred on the consumption of illicit drugs, high and low-risk behavioral drug consumption patterns can be spread because of tight social connections within these communities. The transmission of HIV through needle sharing serves as a primary example of these social connections where disease transmission can occur as a result of social interactions between users in a community [1,31].…”
Section: Peer Association and Drug Usage Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In communities centred on the consumption of illicit drugs, high and low-risk behavioral drug consumption patterns can be spread because of tight social connections within these communities. The transmission of HIV through needle sharing serves as a primary example of these social connections where disease transmission can occur as a result of social interactions between users in a community [1,31].…”
Section: Peer Association and Drug Usage Patternsmentioning
confidence: 99%
“…This type of modelling is rarely used in the field of criminology, yet this method of analyzing complex and dynamic situations is extremely applicable to this field of study [1,2,12,17,30]. The dynamic social behaviors associated with crime and drug use can be successfully represented in a CA model and improve our understanding of the social and related processes tied to the aetiology of disease transmission, drug addiction patterns and behavior modification among the individuals in a high-risk population [1,31].…”
Section: Introductionmentioning
confidence: 98%
“…8,[26][27][28] Other studies have shown associations of syringe sharing with unstable housing 29,30 and public drug use. 31 Syringe sharing may be a marker for those who have more risky behaviors overall, rather than being causally related to overdose. The association between young age and overdose in multivariate Model 1 has been demonstrated in other studies.…”
Section: G001mentioning
confidence: 99%
“…British Columbia stands alone in Canada, as the only jurisdiction showing a steady decline in the rate of HIV new diagnoses. These disparities maybe at least partially attributed to the greater expansion of HAART coverage in British Columbia, especially in the Vancouver Coastal Health Authority [25], as well as the implementation of other HIV prevention interventions, including novel harm reduction strategies aimed at IDUs [26], [27].…”
Section: Discussionmentioning
confidence: 99%